Transformation of Muhammadiyah’s cultural dakwah in perspective of Islam: A literature review on role of dakwah bil-Hal in responding to diversity - Palahuddin Palahuddin; Bayu Karunia Putra (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The cultural dakwah of Muhammadiyah plays a significant role in promoting tolerance and social cohesion in Indonesia’s diverse society. In the context of West Nusa Tenggara, a region marked by ethnic, religious, and cultural diversity, the practice of Dakwah bil-Hal da’wah through actions and real-life examples has emerged as a critical mechanism for addressing intergroup differences and fostering communal harmony. Methods: This study employs a qualitative literature review method, analyzing scholarly articles, policy documents, and organizational reports to examine how Muhammadiyah’s cultural dakwah adapts to and responds to the challenges of diversity in the region. Findings: The findings indicate that Dakwah bil-Hal effectively mediates conflicts and builds tolerance by integrating Islamic ethical principles with local social norms. Muhammadiyah’s initiatives, such as community service, interfaith dialogues, and educational programs, demonstrate that religious practice can actively promote social inclusivity without compromising Islamic values. However, challenges remain in fully institutionalizing these practices across diverse communities and aligning them with governmental diversity policies. Conclusion: The conclusion emphasizes that the integration of cultural dakwah and Dakwah bil-Hal provides a practical model for fostering tolerance and social cohesion in pluralistic societies. Novelty/Originality of this article: The novelty of this article lies in its synthesis of Islamic cultural dakwah theory with empirical insights from West Nusa Tenggara, offering a nuanced perspective on how faith-based initiatives can complement local governance strategies in managing diversity.